Can guilt lead to psychological growth following trauma exposure?. (28th February 2016) - Dekel, Sharon; Mamon, Daria; Solomon, Zahava; Lanman, Olivia; Dishy, Gabriella
Abstract: With the growing interest in posttraumatic growth (PTG) and its predictors, this study examined the relationship between trauma-related guilt and PTG in a sample of veterans over time. Self-reported guilt, PTG, and posttraumatic stress disorder (PTSD) symptoms were measured in combat veterans and prisoners of war (POWs). Positive correlations were found between guilt, PTSD, and PTG levels. Hierarchical regression revealed that initial guilt levels predicted subsequent PTG controlling for initial PTSD in combat veterans but not in POWs. The findings suggest that posttraumatic growth can be facilitated by trauma-related guilt, underscoring the complex relationship between positive and negative trauma outcomes. Highlights: The relationship between posttraumatic growth and distress is not clear. This longitudinal study examines the relation of growth to guilt following trauma. The findings show that guilt may facilitate growth following combat exposure.